Evisceration for the management of ocular trauma. (30th October 2013) - McAlinden, Colm; Saldanha, Mario; Laws, David
Abstract : Despite the eye being surrounded by orbital bones and protective mechanisms such as the blink reflex, it is vulnerable to trauma. The two key issues to consider when presented with a case of ocular trauma are the visual potential of the eye and the risk of sympathetic ophthalmia. The Ocular Trauma Score can be used to assess the visual potential of the injured eye. Surgical management may be either repair or removal of the eye (evisceration or enucleation). Herein we describe a case of ocular trauma and the decision-making process in the management of the injury.